Frequency, Risk Factors, and Clinical Implications of Hypophosphatemia in Critically Ill Patients: A Prospective Observational Study from a Tertiary Care Intensive Care Unit - Tauqeer Ahmad, Muhammad Adnan Iqbal, Uzma Tasneem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypophosphatemia is a frequent but underrecognized electrolyte disturbance in critically ill patients and may contribute to respiratory, cardiovascular, and metabolic dysfunction. Data from low- and middle-income countries remain limited regarding its prevalence, risk factors, and clinical consequences. Objective: To determine the frequency of hypophosphatemia among critically ill patients, identify associated clinical and therapeutic risk factors, and evaluate its relationship with laboratory parameters, ventilatory requirements, and in-hospital mortality. Methods: This prospective observational study was conducted in the Medical Department Allama Iqbal Memorial Teaching Hospital KMSMC Sialkot. One hundred consecutive adult patients were enrolled. Serum phosphate was measured on days 1, 3, and 10 of hospitalization. Hypophosphatemia was defined as serum phosphate <2.5 mg/dL and severe hypophosphatemia as <1.5 mg/dL. Demographic data, diagnoses, medication exposure, ventilatory support, laboratory findings, and outcomes were recorded. Statistical analysis was performed using SPSS version 10. Results: Hypophosphatemia was observed in 16% of patients, while severe hypophosphatemia occurred in 3%. The highest prevalence was noted among patients with diabetic ketoacidosis (27.3%), septicemia (21.9%), and respiratory failure (19%). Hypophosphatemic patients had significantly lower serum calcium and albumin levels (p <0.05). Among non-survivors, 37.5% had hypophosphatemia, and two-thirds required mechanical ventilation. However, serum phosphate levels were not independently associated with mortality. Conclusion: Hypophosphatemia is a common metabolic abnormality in critically ill patients, particularly in those with sepsis, respiratory failure, and diabetic ketoacidosis. Routine monitoring may facilitate early identification and timely correction to support respiratory and metabolic stability. Keywords: Hypophosphatemia, Critical illness, Intensive care unit, Respiratory failure, Electrolyte imbalance